Social impact on project assessment : an integrated methodology for the assessment of investment projects in research and development (R&D) at a society level - Fernández, Ana (2011)
Nowadays, organisations increasingly need to adapt to the fast evolution of markets and societies in our globalised world in order to be competitive. Therefore, it is essential to take the right decisions when it comes to invest in R&D&i projects. The present research focuses not only on the analysis of how R&D&i projects are assessed and selected but also on new proposals to improve them, with the aim of obtaining a suitable methodology which contributes to improve the competitive advantage and to integrate criteria of social nature both in organisations and in the Public Administration. The methodology which has been used in this research includes both interviews and analysis of the data obtained through them.